2024
DOI: 10.3390/vaccines12020182
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Risk of COVID-19-Related Events in Vaccinated Healthcare Workers (HCWs) from a Tertiary Hospital in Bucharest, Romania: A Study Based on Active Surveillance Data

Carmen-Daniela Chivu,
Maria-Dorina Crăciun,
Daniela Pițigoi
et al.

Abstract: Our study describes the frequency and severity of COVID-19 in HCWs and estimates the dynamic risk of COVID-19-related events. We actively surveyed all HCWs from a tertiary infectious disease hospital from 26 February 2020 to 31 May 2023. Of 1220 HCWs, 62.9% (767) had at least one COVID-19 episode. The under 29 years (p = 0.0001) and 40–49 years (p = 0.01) age groups, nurses (p = 0.0001), and high-risk departments (p = 0.037) were characteristics significantly more frequent in HCWs with COVID-19 history. A high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…Natural and artificial immunity has been assessed by evaluating the dynamics of protective antibodies over time or by using epidemiological indicators from surveillance data. Both types of study have shown that natural and artificial immunity both wane over time and have led to the adaptation of recommendations regarding vaccination schedules [ 8 , 17 , 19 , 27 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Common epidemiological indicators of frequency in other studies showed increases in the number of reinfections and primo-infections in the Omicron era, similar to our study [ 25 , 26 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Natural and artificial immunity has been assessed by evaluating the dynamics of protective antibodies over time or by using epidemiological indicators from surveillance data. Both types of study have shown that natural and artificial immunity both wane over time and have led to the adaptation of recommendations regarding vaccination schedules [ 8 , 17 , 19 , 27 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Common epidemiological indicators of frequency in other studies showed increases in the number of reinfections and primo-infections in the Omicron era, similar to our study [ 25 , 26 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of disease history, published studies have supported the importance of hybrid immunity [ 19 , 39 , 49 ]. The study ORCHESTRA compared subjects re-vaccinated with the first booster and a history of SARS-CoV-2 infection with subjects with no prior infection, and the relative risk ratio was 0.11 (95% CI: 0.05–0.25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations